TECHNICAL AND TACTICAL ANALYSIS OF MEN'S 63KG ATHLETE ZHAO SHUAI AT THE 2019 WORLD TAEKWONDO CHAMPIONSHIPS - Lei, Yuan; Hongwei, Yan; Senja, Qonidah Salsabila (Universitas Pendidikan Indonesia, 2022)
Taekwondo is a sport based on physical confrontation. A high level of physical fitness and skills is the basis for the growth of athletes. In Taekwondo competitions, athletes use their skills and tactics to win. This paper aims to make a statistical analysis of the techniques and tactics used by athlete Zhao Shuai in the competition to provide theoretical support and preliminary ideas for this study. The methods used in this research were carefully observing the video, statistical methods and tactical data, scientific preparation, and data use of Zhao Shuai's top 16, top 8, top 4, semi-final, and top 5 in 2019 Manchester World Taekwondo Championships at 63 kg level. The software processing ensures the scientific characteristics of the research data. The results show that technology is the basis of tactics, and tactical development is closely related to technical integrity.